PELATIHAN GURU SEKOLAH DASAR DALAM PENGINTEGRASIAN GAMIFIKASI KE TAHAP-TAHAP PEMBELAJARAN MATEMATIKA - Anita Dewi Utami; Puguh Darmawan; Sapti Wahyuningsih; Abd Qohar (Jurnal Pemantik, 2023)
Gamification is one strategy that can be applied to develop students' interest in learning mathematics. The aim of this training is to introduce gamification to elementary school teachers in learning mathematics, to introduce teaching modules (MA) to elementary teachers who have not yet implemented the independent curriculum, and to train teachers to be able to integrate elements of gamification into MA. This training was held at SD N Penanggungan, Malang City. The training was held on November 20, 2022. The training participants were twenty teachers at SD N Penanggungan. The training was carried out using discussion and question and answer techniques. After that, the presenters accompany the teacher to practice the theory learned by making MA integrated with gamification. The result of this training is that teachers can develop MA that is integrated with gamification. In addition, the teacher is also able to recognize the characteristics of gamification and MA stages that are in accordance with the gamification.